On the Convergence of the Nonnested V-Cycle Multigrid Method for Nonsymmetric and Indefinite Second-Order Elliptic Problems (Journal of Computational Mathematics, 2006)
This paper provides a proof for the uniform convergence rate (independently of the number of mesh levels) for the nonnested V-cycle multigrid method for nonsymmetric and indefinite second-order elliptic problems.
Keywords: Nonnested V-cycle multigrid method; Second-order elliptic problems.